1996
DOI: 10.3354/ame011205
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion and assimilation of carbon from cellulolytic bacteria and heterotrophic flagellates by the mussels Geukensia demissa and Mytilus edulis (Bivalvia, Mollusca)

Abstract: We I4C-labeled cellulolytic bacteria and 3 species of bacterivorous nanoflagellates and fed these cultured organisms to 2 species of intertidal mussels, Geukensia demissa and Mytllus edulis. using a pulse-chase experimental design under controlled laboratory conditions. Ingestion and assimilation of C from these rmcroheterotrophs by mussels were calculated from measured rates of defecation, respiration, excretion, and tlssue incorporation. The proportion of available C ingested by G. demissa did not dlffer sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 25 publications
5
77
0
Order By: Relevance
“…This study confirmed the removal of heterotrophic organisms by juvenile mussels (e.g. Horsted et al 1988, Kreeger & Newell 1996. Assuming that heterotrophs, like phytoplankton, also serve as a food source for mussels (e.g.…”
Section: Recovery Responsesupporting
confidence: 66%
See 1 more Smart Citation
“…This study confirmed the removal of heterotrophic organisms by juvenile mussels (e.g. Horsted et al 1988, Kreeger & Newell 1996. Assuming that heterotrophs, like phytoplankton, also serve as a food source for mussels (e.g.…”
Section: Recovery Responsesupporting
confidence: 66%
“…Heterotrophic organisms can serve as an important food source for bivalves, and filtration can thus result in (local) depletion of heterotrophs like rotifers, heterotrophic nanoflagellates and ciliates (Horsted et al 1988, Kreeger & Newell 1996, Wong et al 2003, Trottet et al 2008a. Since these heterotrophs are the main predators on bacteria and small phytoplankton, the removal of these predators by bivalves might alter the competitive outcome between small and larger algae.…”
Section: Introductionmentioning
confidence: 99%
“…For the clams Macoma balthica and Potamocorbula amurensis, Decho and Luoma (1991) obtained higher C AE values from bacteria than this study-68 and 75%, respectively. For the mussels Geukensia demissa and M. edulis, Kreeger and Newell (1996) measured C AEs of 42 and 21%, respectively, from bacterial diets.…”
Section: Discussionmentioning
confidence: 99%
“…Although phytoplankton was traditionally considered the main food source (Nielsen and Maar 2007), several studies have stated the importance of other food particles like dead organic material (Dame and Dankers 1988) and bacteria attached to this (Newell et al 1989), microzooplankton (Horsted et al 1988;Kreeger and Newell 1996;Trottet et al 2008) and, for larger mussels ([22 mm;Horsted et al 1988), mesozooplankton (Davenport et al 2000;Wong and Levinton 2006;Lehane and Davenport 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Verwey 1952;Cadée and Hegeman 1974;Cloern 1982;Dame 1996;Kreeger and Newell 1996;Wong and Levinton 2006). The recent introduction of mussel seed collectors in the Netherlands prompted the need for assessing the effect of large numbers of juvenile individuals on the carrying capacity of the surrounding ecosystem.…”
Section: Introductionmentioning
confidence: 99%